Genetic Dissection of Nitrogen Use Efficiency in Tropical Maize Through Genome-Wide Association and Genomic Prediction - Ertiro, Berhanu Tadesse; Labuschagne, Maryke; Olsen, Michael; Das, Biswanath; Prasanna, Boddupalli M.; Gowda, Manje (Frontiers in Plant Science, 2020)
In sub-Saharan Africa, one of the major challenges to smallholder farmers is soils with low fertility and inability to apply nitrogen fertilizer externally due to the cost. Development of maize hybrids which performs better in nitrogen depleted soils is one of the promising solutions. However, breeding maize for nitrogen use efficiency (NUE) is hindered by expensive phenotypic evaluations and trait complexity under low N stress. Genome-wide association study (GWAS) and genomic prediction (GP) are promising tools to circumvent this interference. Here, we evaluated a mapping panel in diverse environments both under optimum and low N management. The objective of this study was to identify SNPs significantly associated with grain yield (GY) and other traits through GWAS and assess the potential of GP under low N and optimum conditions. Test cross progenies of 411 inbred lines were planted under optimum and low N conditions in several locations in Africa and Latin America. In all locations, low N fields were previously depleted over several seasons, and no N fertilizer was applied throughout the growing season. All inbred lines were genotyped with genotyping by sequencing. Genotypic and GxE interaction variances were significant and heritability estimates were moderate to high for all traits under both optimum and low N conditions. Genome-wide LD decay at r2=0.2 and r2=0.34 were 0.24 Mbp and 0.19 Mbp, respectively. Chromosome specific LD decays ranged from 0.13 to 0.34 Mbps with an average of 0.22 Mbp at r2 = 0.2. GWAS analyses revealed 38 and 45 significant SNPs under optimum and low N conditions, respectively. Out of these 83 significant SNPs, three SNPs on chromosomes 1, 2 and 6 were associated either with different traits or the same trait under different management conditions, suggesting pleiotropic effects of genes. A total of 136 putative candidate genes were associated with the significant SNPs, of which seven SNPs were linked with four known genes. Prediction accuracies were moderate to high for all traits under both optimum and Low N conditions. These results can be used as useful resources for further applications to develop hybrids or lines with better performance under low N conditions.